"Dile que le he escrito un blues" : del texto como partitura a la partitura como traducción en la literatura latinoamericana - Vidal, M. Carmen Africa (Iberoamericana ; Vervuert Verlag, 2017)
This book addresses the interdisciplinarity of translation as a creative activity and its relationship with music in the context of Latin American literature.